(untitled) (Asian Business Research, 2022)
The rise and prosperity of cross-border e-commerce has brought new development opportunities and great challenges to Chinese enterprises. By discussing the concepts and contents of cross-border e-commerce and enterprise competitiveness, this paper analyzes the influencing factors of enterprise competitiveness of cross-border e-commerce enterprises. By means of questionnaires and interviews with the management of relevant enterprises, the relevant data were obtained. In the dimensional analysis of cross-border e-commerce and enterprise competitiveness, the influencing factors of cross-border e-commerce enterprise competitiveness were discussed. The results show that the flat organizational structure is conducive to enhance the competitiveness of enterprises, and the fund management and human resource management play a more obvious role; The mastery of key technologies brings competitive advantages to enterprises. Because laws and regulations belong to the policy environment, compared with other factors, the impact on the competitiveness of enterprises is not obvious. To sum up, service level and customer satisfaction have the greatest impact on enterprise competitiveness; cost management and capital efficiency have a great impact on the competitiveness of enterprises; The conclusion that market demand has a relatively small impact on enterprise competitiveness.